Analisis Faktor Yang Mempengaruhi Penyerapan Anggaran Pada Pemerintah Daerah Kabupaten Bengkalis - Kennedy Kennedy; Nur Azlina; Julita Julita; Suci Nurulita (Politeknik Caltex Riau, 2020)
Abstract This research aims to examine: the effect of budget planning, quality of human resources, organizational commitment, administrative records, and the government's internal control system on budget absorption. The population in this study was the regional apparatus organization in Bengkalis Regency, which amounted to 35 DPOs, consisting of 1 regional secretariat, 1 DPRD secretariat, 1 inspectorate, 1 civil service police unit, 1 hospital, 7 agencies, and 23 service offices. The method used is saturated sampling, with a total sample of 175 respondents. The data analysis method used in this study is SPSS version 23. The results of this study indicate that budget planning, quality of human resources, organizational commitment, administrative records and government internal control systems significantly influence budget absorption. The results of this research are expected to provide input to DPOs in Bengkalis Regency to take strategic steps in order to increase budget absorption in accordance with targets and regulation. Keywords: Budget Absorption, Budget Planning, Quality of Human Resources, Organizational Commitment, Administrative Records, and Government Internal Control Systems.